UNDERSTANDING OF PROSPECTIVE MATHEMATICS TEACHERS OF THE CONCEPT OF DIAGONAL - Ülkü Ayvaz; Nazan Gündüz; Figen Bozkus (Journal on Mathematics Education, 2017)
This study aims to investigate the concept images of prospective mathematics teachers about the concept of diagonal. With this aim, case study method was used in the study. The participants of the study were consisted of 7 prospective teachers educating at the Department of Mathematics Education. Criterion sampling method was used to select the participants and the criterion was determined as taking the course of geometry in the graduate program. Data was collected in two steps: a diagnostic test form about the definition and features of diagonal was applied to participants firstly and according to the answers of the participants to the diagnostic test form, semi-structured interviews were carried out. Data collected form the diagnostic test form and the semi-structured interviews were analyzed with descriptive analysis. According to the results of the study, it is understood that the prospective teachers had difficulties with the diagonals of parallelogram, rhombus and deltoid. Moreover, it is also seen that the prospective teachers were inadequate to support their ideas with further explanations although they could answer correctly. Ä°t is thought that the inadequacy of the prospective teachers stems from the inadequacy related to proof.DOI:Â http://dx.doi.org/10.22342/jme.8.2.4102.165-184